Reversible hydration of CH(3)NH(3)Pbl(3) in films, single crystals, and solar cells - Leguy,AMA; Hu,Y; Campoy-Quiles,M; Isabel,Alonso M; Weber,OJ; Azarhoosh,P; van,Schilfgaarde M; Weller,MT; Bein,T; Nelson,J; Docampo,P; Barnes,PRF (Chemistry of Materials, 2015)
Solar cells composed of methylammonium lead iodide perovskite (MAPI) are notorious for their sensitivity to moisture. We show that (i) hydrated crystal phases are formed when MAPI is exposed to water vapor at room temperature and (ii) these phase changes are fully reversed when the material is subsequently dried. The reversible formation of CH3NH3PbI3·H2O followed by (CH3NH3)4PbI6·2H2O (upon long exposure times) was observed using time-resolved XRD and ellipsometry of thin films prepared using “solvent engineering”, single crystals, and state-of-the-art solar cells. In contrast to water vapor, the presence of liquid water results in the irreversible decomposition of MAPI to form PbI2. MAPI changes from dark brown to transparent on hydration; the precise optical constants of CH3NH3PbI3·H2O formed on single crystals were determined, with a bandgap at 3.1 eV. Using the single-crystal optical constants and thin-film ellipsometry measurements, the time-dependent changes to MAPI films exposed to moisture were modeled. The results suggest that the monohydrate phase forms independent of the depth in the film, suggesting rapid transport of water molecules along grain boundaries. Vapor-phase hydration of an unencapsulated solar cell (initially Jsc ≈ 19 mA cm–2 and Voc ≈ 1.05 V at 1 sun) resulted in more than a 90% drop in short-circuit photocurrent and ∼200 mV loss in open-circuit potential; however, these losses were fully reversed after the device was exposed to dry nitrogen for 6 h. Hysteresis in the current–voltage characteristics was significantly increased after this dehydration, which may be related to changes in the defect density and morphology of MAPI following recrystallization from the hydrate. Based on our observations, we suggest that irreversible decomposition of MAPI in the presence of water vapor only occurs significantly once a grain has been fully converted to the monohydrate phase.